Overview of Animal Manure Management for Beef, Pig, and Poultry Farms in France - Loyon, Laurence (Frontiers in Sustainable Food Systems, 2018)
This paper brings together the available data relating to pig, cattle and poultry manure management in France. Cattle, pig and poultry livestock produce around 120 million tons of manure per year. The most common method of manure management is storage (in building and pit) and spreading. Solid manure is mainly stored in temporary field heaps. The capacity storage on farm varies from 45 days to 7.5 months. Treatment applies to 13.6 million tons of the manure produced. Nitrogen applied as slurry is mostly spread on the soil surface using splash plate tankers. The treatment of manure and the use of specific techniques to reduce gaseous emissions (such as frequent manure removal from buildings, storage covers or injection) are not widely reported.